Intracranial Glioblastoma with Drop Metastases to the Spine After Stereotactic Biopsy - Albert, Gregory; Wassef, Shafik; Dahdaleh, Nader; Lindley, Timothy; Bruch, Leslie; Hitchon, Patrick (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background Glioblastoma (GBM) is the most common primary intracranial tumor, but metastases are rarely reported. Previous reports have documented the occurrence of drop metastases to the spine. However, few of these reports have demonstrated the occurrence of spinal metastases after biopsy with stable intracranial disease. Here we present such a case.Case Description We present a case of GBM metastatic to the spinal cord after a stereotactic biopsy with stable intracranial disease. To our knowledge, this occurrence has only been reported in one previous case.Conclusion We propose that traversing the lateral ventricle at the time of biopsy contributed to cerebrospinal fluid seeding with tumor cells and subsequent development of spinal disease.
Keywords: glioblastoma; GBM; metastasis; spine